Influence of abiotic stress during soybean germination followed by recovery on the phenolic compounds of radicles and their antioxidant capacity - Sylwia Swigonska; Ryszard Amarowicz; Angelika Król; Agnieszka Mostek; Anna Badowiec; Stanisław Weidner (Acta Societatis Botanicorum Poloniae, 2014)
Abiotic stress factors are among the major causes of lower crop yields. It is known, that in response to cold and/or osmotic stress, crops activate various defense mechanisms, including morphological, physiological and metabolic adaptations. Secondary metabolism, especially phenolic compounds, seem to be an important factor of stress-induced metabolic re-engineering as their levels are alternated by abiotic stress in plants. Despite the fact, that the nature and function of phenolic compounds was already studied in various plant species, it is important to define tissue-specific changes induced by two most potent abiotic stressors – low temperature and decreased water potential. Moreover, in fields, the appearance of single stress is rather rare. Usually two or more factors are acting in parallel, which may potentially result in different effects. Therefore, the aim of this study was to analyze selected elements of secondary metabolism in roots of germinating soybean seeds under cold stress, osmotic stress and both stresses combined. In addition the effects of constant and persistent stress were compared to those induced by sudden and brief stress appearance, as well as after the post-stress recovery process. In the presented study standard methods for identification and quantification of phenolic acids and isoflavones were used and the antioxidant capacity of the radicle extracts was measured. The phenolic metabolism in plants was greatly intensified in response to cold and osmotic stress and remained at high level during the post-stress recovery. The amount and composition of both phenolic acids and identified isoflavones also changed in stress- and duration-dependent manner. This proves an important role of phenolic compounds in abiotic stress response of germinating soybean seeds and opens up new perspectives for further investigations.